ANALISA DAN DESAIN SISTEM INFORMASI ADMINISTRASI RAWAT JALAN STUDI KASUS: BIDAN EBO MASIH, S.SIT - Samsinar; Arya Fathoni (Jurnal Maklumatika, 2015)
Bidan Ebo Masih, S.SIT is an institution providing medical service for public. The patient dataprocessing transaction system, including that of patients having the ongoing checkup process, is stilldone manually. This results on late monthly report. In order to solve the issue, the writer uses object-oriented methodology by (1) developing Use Case Diagram, Sequence Diagram, Activity Diagram,Class Diagram, and Fishbone Diagram, and also the desktop design as the interface, (2) makingreport as the decision making and to implement it using VB.NET 2008 as programming language, and(3) using MySQL as database. One way to ease the performance is by using it on the services foroutpatients with fast and accurate procedure which could reach each patient’s satisfaction. The writerhopes that this computerized information system design on outpatient administration would help BidanEbo Masih, S.SIT in solving the regular problems.